Analysis of Student Needs in the Development of TPACK-Based English Syllabus and Learning Plans - Juni Hartiwi; Desti Nurdianti; Adhi Nurhartanto; Astirini Swarastuti; Rian Sigit Gesang Permana; Sandi Pradana (LinguaScopes: International Journal of Language Education, 2026)
The use of digital tools in English as a foreign language (EFL) classrooms is growing rapidly, but systematic evidence of what students really need from technology-based learning is still limited. As a result, curriculum developers often choose digital resources based on availability, rather than the results of the diagnosis. This study analyzes the need to prepare a syllabus and lesson plan based on the Technological Pedagogical Content Knowledge (TPACK) framework. Using an exploratory sequential mixed-methods design, data were collected through a Likert scale questionnaire of 214 EFL high school students, a focus group discussion with 18 student representatives, a semi-structured interview with nine English teachers, and a document analysis of twelve syllabus and forty-five lesson plans. Quantitative data are analyzed with descriptive statistics (mean, frequency, percentage); Qualitative data were analyzed using Miles and Huberman's interactive model in the form of data reduction, data presentation, and conclusion drawn. Results showed prominent difficulties in listening and speaking skills (M = 4.21 and 4.05 on a difficulty scale of 1-5), strong preference for interactive video and mobile-based learning (61% combined), as well as large gaps between teachers' current TPACK practices and student expectations, especially in the integrated TPACK dimension (teachers M = 2.2 versus student expectations M = 4.7). These findings are synthesized into a curriculum blueprint that positions technology as a pedagogical mediator, not a substitute for content. This study contributes a replicable empirical procedure for translating needs analysis data into a TPACK-based curriculum document, while offering methodological templates and substantive design principles for EFL syllabus developers.